Visualisasi Company Profil 3D Bangunan Ria Busana Sebagai Media Promosi Berbasis Augmented Reality Menggunakan Google Sketch Up - Wahyuda Adios Zul Pratama; Suriati; Siti Sundari (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Ria Busana is a national-scale fashion retail company spread across several cities in Indonesia. Fashion retailer that serves clothes to accessories ranging from babies, children, women and adult men with superior products according to trends, quality and affordable prices. The use of information media at Ria Busana is still manual, one of which is the Ria Busana profile so that researchers have a proposal to design Augmented Reality- based 3-dimensional animation into an android application. Making this android application using Unity3D and Vuforia software for making Ria Busana building models using Google SketchUp software. Starting from data collection, makig process of making QR barcode to the final result. After Augmented Reality can be used, building objects can be replaced in the form of markers, markers are patterns made in the form of images that will be recognized by the camera. The final result of this research is based on Augmented Reality which can visualize 3-dimensional objects of the Ria Busana building which has been successfully used for promotional media.